The Secretome of Filarial Nematodes and Its Role in Host-Parasite Interactions and Pathogenicity in Onchocerciasis-Associated Epilepsy - Hotterbeekx, An; Perneel, Jolien; Vieri, Melissa Krizia; Colebunders, Robert; Kumar-Singh, Samir (Frontiers in Cellular and Infection Microbiology, 2021)
Filarial nematodes secrete bioactive molecules which are of interest as potential mediators for manipulating host biology, as they are readily available at the host-parasite interface. The adult parasites can survive for years in the mammalian host, due to their successful modulation of the host immune system and most of these immunomodulatory strategies are based on soluble mediators excreted by the parasite. The secretome of filarial nematodes is a key player in both infection and pathology, making them an interesting target for further investigation. This review summarises the current knowledge regarding the components of the excretory-secretory products (ESPs) of filarial parasites and their bioactive functions in the human host. In addition, the pathogenic potential of the identified components, which are mostly proteins, in the pathophysiology of onchocerciasis-associated epilepsy is discussed.